Efficacy of MRI and clinical findings of Lidocaine injection combined with manual therapy in frozen shoulder—A prospective, randomized, single-blinded, sham-controlled trial - Gopal Nambi; Mshari Alghadier; Elturabi Elsayed Ebrahim; Mudathir Mohamedahmed Eltayeb; Dena Eltabey Sobeh; Osama R. Aldhafian; Shahul Hameed Pakkir Mohamed; Naif Nwihadh Alshahrani; Faizan Z. Kashoo; Hariraja Muthusamy; Radhakrishnan Unnikrishnan; Alaa Jameel A. Albarakati (PLoS ONE, 2025)
Background Frozen shoulder, or adhesive capsulitis, is a debilitating condition characterized by progressive pain and restricted range of motion in the glenohumeral joint. A wide range of interventions has been explored for its management, including conservative physiotherapy approaches such as thermotherapy, manual therapy, and therapeutic exercises. Pharmacological interventions, including pain medications, and muscle relaxants are commonly employed to alleviate symptoms. Additionally, intra-articular corticosteroid injections have been shown to provide short-term relief. While each modality offers potential benefits, the optimal treatment strategy remains a subject of ongoing investigation. Purpose The objective of this study is to investigate the clinical and magnetic resonance image (MRI) changes after lidocaine injection with manual therapy in frozen shoulder. Study design/ setting Randomized, single-blinded controlled study conducted at University hospital. Patient sample Sixty eligible participants were divided into an active group (n = 30; Lidocaine injection with active manual therapy) and the placebo group (n = 30; Lidocaine injection with placebo manual therapy) 4 sessions per week for 4 weeks. Outcome measures The primary outcome was pain intensity, measured with the visual analogue scale and the other outcome measures were range of motion (ROM), functional disability, thickness of corocohumeral ligament (CHL) by MRI, and quality of life which was measured at baseline, after 4 weeks, 8 weeks and at 6 months. Results The VAS score at 4 weeks shows an improvement 2.4 (CI 95% 2.08 to 2.71) in the active group than the placebo group. Similar effects have been noted after 8 weeks 3.0 (CI95% 2.68 to 3.31) and at 6 months 2.5 (CI95% 2.18 to 2.81). Similar statistically significant improvements were found in the ROM (abduction & Lateral rotation), functional disability, thickness of CHL ligament, status and quality of life (p = 0.001). Conclusion Lidocaine injection with active manual therapy consists of scapula mobilization and posterior capsular stretching was superior to placebo group for improving pain, ROM, functional disability, and quality of life in people with frozen shoulder. Trial registration ClinicalTrials.gov CTRI/2020/04/024853